(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, priority directions for the development of eco-aesthetic culture in future preschool education specialists, implementation of eco-aesthetic culture development of future preschool education system pedagogues in the process of ecological education and upbringing, and ecological-aesthetic outlook in future pedagogues-educators opinions on the development of eco-aesthetic culture through formation are presented.